The Influence of English Expressions on The T-Shirt towards Young Generations in Makassar - Sumirna Sumirna; Andi Hudriati; Risty Aristyanty (Fakultas Sastra - Universitas Muslim Indonesia, 2017)
The research objectives are to know the grammaticality English expressions on the T-shirt. To get the information effects of good message contents of slogan are discovered in young generations’ T-shirt. To get the information effects of bad message contents of slogan are discovered in young generations’ T-shirt In this thesis, the writer used descriptive method to take the sample. Then, the writer observed the expression in the several access areas and explained the opinions by young generations, till it can take some causes of the effect. Hereafter, the research processed the data by analyzing carefully. The finding of this research, it has result the statements of the grammaticality are rarely to use it. It usually written is non-standard in English such as: deliberate misspelling, slang. Then, good and bad effect can be covered into our feeling like: being proud, confidence, motivated, etc. so, it can arrangement our mindset even our act.